Relationship between training load and recovery in collegiate American football players during preseason training - Jagim, A. R.; Wright, G. A.; Camic, C. L.; Nisiolek, J. N.; Luedke, J.; Oliver, J. M.; Fischer, K. M.; Jones, M. T. (Science and Medicine in Football, 2021)
Background: The purpose of this study was to examine the relationship between training load and nextday recovery in collegiate American football (AF) players during pre-season. Methods: Seventeen athletes (Linemen, n = 6; Non-linemen, n = 11) participated in the 14-day study wearing monitoring (accelerometer + heart rate) sensors during on-field practice sessions throughout pre-season to assess the physiological (PL), mechanical load (ML) and recording of session RPE (sRPE load) immediately post-practice. Prior to practice, participants completed a drop-jump reactive strength index (RSI) test and reported perceived recovery status (PRS). Loaded counter movement vertical jump was assessed before and after pre-season. Results: For every one unit increase in sRPE load, RSI declined by 0.03. Non-linemen had a lower RSI value of 73.1 units compared to linemen. For every one unit increase in ML, the PRS decreased by 0.01. Nonlinemen recorded higher average ML during week 2 (ES = 1.17) compared to linemen. Non-linemen recorded higher RSI values in weeks 1 (ES = -1.41) and 2 (ES = -1.72) compared to linemen. All training load and recovery parameters were lower week 2 compared to week 1 (p < 0.05) for all players. Conclusions: Next-day RSI values were influenced by sRPE load while next-day PRS appears to be more influenced by ML. No difference in PL or sRPE load was observed been groups despite non-linemen completing a higher ML throughout the preseason. A combination of training load and recovery metrics may be needed to monitor the fatigue and state of readiness of each player.